2010
DOI: 10.1007/s12034-010-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Lead adsorption study on combustion derived γ-Fe2O3 surface

Abstract: New combustion synthetic route for the synthesis of nanosized γ-Fe 2 O 3 by microwave-assisted route is reported. X-ray density, tap density and powder density of prepared γ-Fe 2 O 3 are calculated. Adsorption study of Pb 2+ on combustion derived nanosized γ-Fe 2 O 3 is studied by dynamic method. The γ-Fe 2 O 3 structure and lead adsorbed γ-Fe 2 O 3 (Pb-γ-Fe 2 O 3 ) are studied by X-ray diffraction (XRD). Additional lead peaks in Pb-γ-Fe 2 O 3 sample pattern confirm the lead adsorption. Morphology of as prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The uptake of Cr(VI) ions by different transition metal spinel ferrites was studied by Hu et al [15]. The adsorption of Pb(II) by γ -Fe 2 O 3 was explored by Lagashetty et al [16]. Ren et al [17] studied the adsorption of Pb(II) and Cu(II) from aqueous solution on magnetic porous ferrospinel MnFe 2 O 4 prepared by a sol-gel process.…”
Section: Introductionmentioning
confidence: 99%
“…The uptake of Cr(VI) ions by different transition metal spinel ferrites was studied by Hu et al [15]. The adsorption of Pb(II) by γ -Fe 2 O 3 was explored by Lagashetty et al [16]. Ren et al [17] studied the adsorption of Pb(II) and Cu(II) from aqueous solution on magnetic porous ferrospinel MnFe 2 O 4 prepared by a sol-gel process.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the combustion process favors the retention of metallic chemical species on adsorbent solids due to their improved textural characteristics. 9,10 Materials prepared by chemical combustion have attracted increasing interest because of their novel properties and potential technological applications (e.g., adsorption, adhesion, surface diffusion, and catalysis). The adsorption process with chemical combustion prepared materials has significant advantages over chemical precipitation, coagulation, chemical oxidation and reduction, ion exchange, reverse osmosis, membrane processes, filtration and other separation technologies reported in the specialized literature, [11][12][13] due to lower operation cost, high selectivity, high efficiency in removing very low levels of heavy metals from dilute solutions and easy handling.…”
Section: Introductionmentioning
confidence: 99%
“…High‐temperature synthesis, sol–gel, hydrothermal, solution‐combustion synthesis, and microwave synthesis, among other methods, have been reported in the literature for the preparation of diverse materials . In recent years, inorganic materials have attracted much interest due to their potential applications as adsorbents in wastewater treatment . On the other hand, the undesirable presence of a great amount of toxic or radioactive metals in water has reached important levels in the recent years; therefore, the suitable disposition and treatment of these materials is of great interest.…”
Section: Introductionmentioning
confidence: 99%